DIFFERENTIAL SENSITIVITY EVALUATION OF MCF-7 AND MDA-MB-231 HUMAN BREAST CANCER CELLS EXPOSED TO TAMOXIFEN ALONE AND IN COMBINATION WITH ESTRADIOL - P. MCFADDEN; S.K. MAJUMDAR (International Journal of Pharma and Bio Sciences, 2012)
The comparative cytotoxic effects of Tamoxifen (TAM) alone or with Estradiol (ES) were studied in estrogen receptor alpha positive (ERα+) MCF-7 and estrogen receptor alpha negative (ERα-) MDA-MB-231 human breast cancer cell lines in vitro using cell proliferation, viability, and clonability assays. The cells were incubated with 5 or 7.5μg/mL TAM with or without 0.5μg/mL ES and treated for 24, 48, 72, and 96 hours for cell multiplication and viability. For cloning, the cells were treated similarly, but studied at 96 and 120 hours. In general, MCF-7 cells compared to MDA-MB-231 cells were more sensitive to TAM treatment as evident from cell replication, viability, and clonability. As expected, 7.5μg/mL was more toxic in both cell lines, but more noticeable in ERα+ MCF-7 cells 48 hours post treatment. Estradiol treatment, in general improved the cell multiplication and viability in both cell lines. Although TAM treatments suppressed cloning ability significantly in both cell lines, the effect was less pronounced in MDA-MB-231. The ES and TAM combination treatment further inhibited colony formation. In conclusion, the two cell lines demonstrated differential sensitivity to TAM with or without ES as revealed from cell proliferation and clonability studies.